RISK OF DEVELOPING EATING DISORDERS ASSOCIATED WITH NUTRITIONAL STATUS, AGE AND SEX IN UNIVERSITY STUDENTS: TRANSTORNOS ALIMENTARES ASSOCIADOS AO ESTADO NUTRICIONAL (REMUNOM, 2025)
Introduction: Eating disorders (EDs) are serious psychiatric disorders that affect eating behavior and body image. College students are at higher risk for EDs due to biopsychosocial changes, such as academic stress, multiple responsibilities, and transition to adulthood, negatively impacting physical and mental health. Objective: Verifying the association between the risk of developing EDs and nutritional status, sex, and age in college students. Methodology: Quantitative, descriptive, and cross-sectional study that evaluated 488 college students of both sexes, from a university in a city in Rio Grande do Sul. Data collection took place from 2022 to 2024, online, through the EAT-26 questionnaire, which assesses the risk for EDs. In addition, information on weight, height, age, and current course were collected. Nutritional status was calculated by the Body Mass Index (BMI), according to the criteria established by the World Health Organization (WHO, 1995). The study was approved by the Research Ethics Committee: under numbers 4,911,923, 5,833,619 and 6,671,468. The statistical test used was the non-parametric Mann-Whitney test. Results: Students at risk of EDs had significantly higher mean weight and BMI than those without risk (p=0.014 and p=0.001), respectively. There was no significant association with age (p=0.580). Females had a higher frequency of risk of EDs (p=0.044). Conclusion: The risk of EDs was associated with females, health care professionals and excess weight. This reinforces the need for preventive actions and nutritional and psychological monitoring aimed at this population, in order to reduce risk factors and promote a healthier relationship with the body and food.